Editorial Note - Suvi Rautio (Suomen Antropologi)
Happy 2025, readers! It gives me great pleasure to present this year’s Winter Issue of Suomen antropologi: Journal of the Finnish Anthropological Society. This issue contains three peer-reviewed articles, three book review essays, and four research reports.